2017
DOI: 10.1007/s10151-017-1586-z
|View full text |Cite
|
Sign up to set email alerts
|

T1 colon cancer in the era of screening: risk factors and treatment

Abstract: Some factors associated with an increase in detection of positive LN were identified. However, further studies are needed to identify more sensitive markers and avoid surgical overtreatment. There is a need to raise the minimum LN count and to use the LN count as an indicator of surgical quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We still observed a fairly high surgery referral rate (27.6%) among patients with well characterised low-risk cancerized adenomas. Many studies [21,22,31,32] documented that endoscopic removal of these lesions is associated with very low rates of recurrence and with a high disease-free and overall survival, often approaching 100% at five-year follow-up, while surgical treatment may be associated with a high potential for morbidity. According to our data, about 15% of patients experienced post-surgery complications, with a significant increase of direct and indirect costs.…”
Section: Residual Disease and Nodal Involvementmentioning
confidence: 99%
“…We still observed a fairly high surgery referral rate (27.6%) among patients with well characterised low-risk cancerized adenomas. Many studies [21,22,31,32] documented that endoscopic removal of these lesions is associated with very low rates of recurrence and with a high disease-free and overall survival, often approaching 100% at five-year follow-up, while surgical treatment may be associated with a high potential for morbidity. According to our data, about 15% of patients experienced post-surgery complications, with a significant increase of direct and indirect costs.…”
Section: Residual Disease and Nodal Involvementmentioning
confidence: 99%
“…From these articles, 90 articles were excluded because the papers were not in English or Chinese (n=2), had unavailable data (n=23) and were unrelated (n=65). Finally, 54 studies were included, with 30 included in the systematic review,5 19–47 and 24 in the meta-analysis (figure 1). 12–14 48–68…”
Section: Resultsmentioning
confidence: 99%
“…In the systematic review, 20 articles revealed no significant association between age and the retrieval of LNs in colorectal cancer 21–23 26 27 30 32 35 37–41 47–49 54 55 64 65. However, 18 articles indicated that more LNs were obtained from young patients than elderly patients (online supplemental table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is insufficient evidence regarding long-term outcomes of patients with surgically resected T1 CRC in heterogeneous Western populations [ 16 ]. Predictive factors such as lymphovascular invasion, tumor budding, and submucosal invasion depth are difficult to assess after endoscopic therapies [ 17 ]. Conversely, homogeneous patient and tumor characteristics might provide more appropriate indicators for the treatment of T1 CRC.…”
Section: Introductionmentioning
confidence: 99%